Electron transport study of indium oxide as photoanode in DSSCs: A review. (September 2016) - Mahalingam, S.; Abdullah, H.
Abstract: In2 O3 materials are rarely used as photoanode in dye-sensitized solar cells (DSSCs). The morphology and properties of In2 O3 influences the overall power conversion efficiency (PCE) of the DSSCs. In2 O3 nanotubes with one dimensional structure enhance the charge collection efficiency by providing direct transport pathway in DSSCs. In addition, the large surface area with hollow porous structure improves dye loading that increases the PCE. Moreover, the reasons for poor performance in In2 O3 -based DSSCs were also reviewed. Even though, the cell achieves a high Jsc, the Voc is still low. The main reason for this event is the injected electrons which are forced to drive a large force with a great energy gap between CB and LUMO of dye that leads to a high Jsc . While, the In2 O3 materials with more positive potentials causes the Voc to decrease. Increasing the energy band gap of In2 O3 is one of the solution to increase the Voc in the DSSCs. The review ends by analyzing the electron transport parameters of Rct, Rt, Cµ, τeff, Deff, and Ln . Investigating the electron transport properties may boost the light harvesting efficiency of In2 O3 -based DSSCs.